Making 'Noise' Online: An Analysis of the Say No to Terror Online Campaign - Aly, Anne; Weimann-Saks, D.; Weimann, G. (Terrorism Research Initiative and the Center for Terrorism and Security Studies, 2014)
A consideration of terrorism as communication necessarily draws attention to the development of counter narratives as a strategy for interrupting the process by which individuals become radicalised towards violent extremism. As the Internet has become a critical medium for psychological warfare by terrorists, some attempts have been made to challenge terroristic narratives through online social marketing and public information campaigns that offer alternative narratives to the terrorists’ online audiences. ‘Say No to Terror’ is one such campaign. This article reports on a study that examined the master narratives in the ‘Say No to Terror’ online campaign and applied concepts of ‘noise’ and persuasion in order to assess whether the key elements of the ‘Say No to Terror’ campaign align with the application of “noise” as a counter strategy against terrorists’ appeal on the Internet. The study found that while the master narratives of ‘Say No to Terror’ align with suggestions based on empirical research for the development of effective counter campaigns, the campaign does not meet the essential criteria for effective noise.